The SlCBL10 Calcineurin B-Like Protein Ensures Plant Growth under Salt Stress by Regulating Na+ and Ca2+ Homeostasis. Issue 2 (11th December 2017) - Egea, Isabel; Pineda, Benito; Ortíz-Atienza, Ana; Plasencia, Félix A.; Drevensek, Stéphanie; García-Sogo, Begoña; Yuste-Lisbona, Fernando J.; Barrero-Gil, Javier; Atarés, Alejandro; Flores, Francisco B.; Barneche, Fredy; Angosto, Trinidad; et al.
Abstract : Tomato CALCINEURIN B-LIKE PROTEIN 10 (SlCBL10) ensures plant growth by regulating proper distribution of Na+ and Ca2+ in the shoot apical meristem and developing organs under salt stress. Abstract: Characterization of a new tomato ( Solanum lycopersicum ) T-DNA mutant allowed for the isolation of the CALCINEURIN B-LIKE PROTEIN 10 ( SlCBL10 ) gene whose lack of function was responsible for the severe alterations observed in the shoot apex and reproductive organs under salinity conditions. Physiological studies proved that SlCBL10 gene is required to maintain a proper low Na + /Ca 2+ ratio in growing tissues allowing tomato growth under salt stress. Expression analysis of the main responsible genes for Na + compartmentalization (i.e. Na + /H + EXCHANGERs, SALT OVERLY SENSITIVE, HIGH-AFFINITY K+ TRANSPORTER 1;2, H + -pyrophosphatase AVP1 [ SlAVP1 ] and V-ATPase [ SlVHA-A1 ]) supported a reduced capacity to accumulate Na + in Slcbl10 mutant leaves, which resulted in a lower uploading of Na + from xylem, allowing the toxic ion to reach apex and flowers. Likewise, the tomato CATION EXCHANGER 1 and TWO-PORE CHANNEL 1 ( SlTPC1 ), key genes for Ca 2+ fluxes to the vacuole, showed abnormal expression in Slcbl10 plants indicating an impaired Ca 2+ release from vacuole. Additionally, complementation assay revealed that SlCBL10 is a true ortholog of the Arabidopsis ( Arabidopsis thaliana ) CBL10 gene, supporting that the essential function of CBL10 is conserved in Arabidopsis and tomato. Together, the findings obtained in this study provide new insights into the function of SlCBL10 in salt stress tolerance. Thus, it is proposed that SlCBL10 mediates salt tolerance by regulating Na + and Ca 2+ fluxes in the vacuole, cooperating with the vacuolar cation channel SlTPC1 and the two vacuolar H + -pumps, SlAVP1 and SlVHA-A1, which in turn are revealed as potential targets of SlCBL10 .